2018
DOI: 10.1039/c8tc03527j
|View full text |Cite
|
Sign up to set email alerts
|

Bond valences and anharmonicity in vacancy-ordered double perovskite halides

Abstract: Anharmonicity is observed in vacancy-ordered double perovskites when the A-site cation is not optimally coordinated by the octahedral framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…Recently, X-ray pair distribution function analysis on Cs2SnI6 has revealed asymmetry in the interoctahedral I−I distance, which can be correlated with rotational disorder for the isolated SnI6 octahedral units, but the technique does not provide information about the activation energy associated with this rotation. 81,82 Therefore, variable-temperature 119 Sn NMR measurements were carried out on a solvent-synthesized Cs2SnI6 sample to probe specifically the anharmonicity of the isolated octahedral SnI6 units to determine the associated activation energies needed for this unique property.…”
Section: Sni6 Octahedral Dynamics In Cs2sni6mentioning
confidence: 99%
“…Recently, X-ray pair distribution function analysis on Cs2SnI6 has revealed asymmetry in the interoctahedral I−I distance, which can be correlated with rotational disorder for the isolated SnI6 octahedral units, but the technique does not provide information about the activation energy associated with this rotation. 81,82 Therefore, variable-temperature 119 Sn NMR measurements were carried out on a solvent-synthesized Cs2SnI6 sample to probe specifically the anharmonicity of the isolated octahedral SnI6 units to determine the associated activation energies needed for this unique property.…”
Section: Sni6 Octahedral Dynamics In Cs2sni6mentioning
confidence: 99%
“…The structure is derived from conventional perovskites by doubling the ABX 3 unit cell along all three crystallographic axes and removing every other B-site cation to form a face-centered lattice of isolated BX 6 octahedral units bridged by A-site cations in the void (vacancy-ordered DHPs). [18,19] The absence of one B-site cation in the double perovskite A 2 B 2 X 6 yields the vacancy-ordered double perovskite structure, [20] as illustrated in the schematic diagram in Figure 2. The A 2 BX 6 structure shows similar features to ABX 3 perovskites, mostly of cubic structures.…”
Section: Introductionmentioning
confidence: 99%
“…The weak bonding allows the atoms to vibrate with a large frequency in the case of the Cs atom, whereas the vibrations in I and Sn occur with smaller frequencies due to the stronger bonding interaction. A neutron diffraction study conducted recently by Maughan et al, to investigate the anharmonicity in vacancy-ordered double perovskite halides (Cs 2 Sn 1– x Te x I 6 ), showed that, by increasing the temperature, atomic displacements of Cs atoms were higher than those of I and Sn, specifically when x = 0 . Accordingly, the Cs atoms act as scattering centers, which negatively influence the phonon propagation pathway, while the vibration of strongly bonded atoms (I and Sn) forms small ducts for phonon propagation.…”
Section: Resultsmentioning
confidence: 99%